Micro-nano cobaltosic oxide and preparation method thereof
Patent Information
- Application Number
- CN202611332372.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]有鉴于此,本申请提供一种微纳级四氧化三钴及其制备方法,用于解决碳酸钴中间品因重结晶导致煅烧后四氧化三钴粒径增大,进而导致作为高镍三元正极材料表面添加剂时首圈容量和首效降低的问题
[0016]本申请的有益效果如下:本申请中以碳酸钠替代碳酸氢铵作为沉淀剂,避免了含氨原料的使用,从而降低了废水处理及环保成本;同时,以碳酸钴作为中间品替代氢氧化钴制备微纳级四氧化三钴,碳酸钴在煅烧过程中不易发生氧化和板结,能够获得钴含量稳定的产物。此外,通过在反应体系中加入分散剂,利用分散剂的吸附和空间位阻作用抑制碳酸钴颗粒间的团聚与重结晶生长,避免了碳酸钴因重结晶特性在放置过程中生成大颗粒的问题,使得产物能够长时间维持均匀的微纳级形貌。
Smart Images

Figure CN122877816A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode materials technology, and in particular to a micro / nano-scale cobalt tetroxide and its preparation method. Background Technology
[0002] High-nickel ternary cathode materials have become an important development direction for lithium-ion battery cathode materials due to their high discharge specific capacity. However, with the increase of nickel content and charging cutoff voltage, the residual alkali on the cathode material surface increases, and the material structure is easily damaged under high voltage, resulting in a significant reduction in cycle life. To solve these problems, industrially, micro- and nano-scale oxides are usually coated or doped on the surface of the cathode material. Among them, micro- and nano-scale cobalt tetroxide is widely used as a surface additive for high-nickel ternary cathode materials due to its good electrochemical stability and lattice matching with ternary materials.
[0003] Currently, the preparation of micro / nano-scale cobalt tetroxide typically uses cobalt carbonate or cobalt hydroxide as precursors, obtained through calcination. Cobalt carbonate, compared to cobalt hydroxide, offers advantages such as resistance to oxidation and caking, and the cobalt content of the calcined product remains stable. Industrially, cobalt carbonate is usually produced by the precipitation reaction of cobalt salts with carbonates (such as sodium carbonate and ammonium bicarbonate). To avoid wastewater treatment and environmental costs associated with ammonia-containing raw materials, using sodium carbonate instead of ammonium bicarbonate as a precipitant has become a research direction in this field. However, when using sodium carbonate as a precipitant to prepare cobalt carbonate, due to its recrystallization characteristics, cobalt carbonate gradually undergoes crystal growth during the post-reaction storage period, resulting in large particles after more than 8 hours of storage. These large particles, after calcination, form cobalt tetroxide with increased particle size, losing their micro / nano-scale characteristics. This directly leads to uneven surface coating when used as a surface additive in high-nickel ternary cathode materials, resulting in a significant decrease in initial capacity and initial coulombic efficiency.
[0004] In view of this, this application provides a micro-nano grade cobalt tetroxide and its preparation method, which solves the technical problem that the particle size of cobalt tetroxide increases after calcination due to recrystallization of cobalt carbonate intermediates, thereby reducing the first-cycle capacity and first-cycle efficiency when used as a surface additive for high-nickel ternary cathode materials. Summary of the Invention
[0005] In view of this, this application provides a micro-nano grade cobalt tetroxide and its preparation method, which solves the problem that the particle size of cobalt tetroxide increases after calcination due to recrystallization of cobalt carbonate intermediates, which in turn leads to a decrease in the first-cycle capacity and first-cycle efficiency when used as a surface additive for high-nickel ternary cathode materials.
[0006] To achieve the above technical objectives, this application adopts the following technical solution: In a first aspect, this application provides a method for preparing micro / nano-scale cobalt tetroxide, comprising the following steps: Using sodium carbonate solution as the base liquid, a dispersant is added and stirred. Then, a cobalt salt solution is added and reacted at a constant temperature. The reaction product is separated into solid and liquid, dried, calcined, cooled, crushed, and sieved to obtain micro-nano grade cobalt tetroxide.
[0007] Preferably, the concentration of the sodium carbonate solution is 100-200 g / L, and the amount used is 4000-5000 L.
[0008] Preferably, the cobalt salt is cobalt chloride; the concentration of the cobalt salt solution is 90-100 g / L, and the amount used is 1800-2000 L.
[0009] Preferably, the stirring speed is 400-500 rpm.
[0010] Preferably, the dispersant is sodium dodecyl sulfonate or sodium hexametaphosphate.
[0011] Preferably, the amount of dispersant used is 6-10 kg.
[0012] Preferably, the temperature for the isothermal reaction is 40-60℃.
[0013] Preferably, the drying temperature is 100-120℃ and the drying time is 8-10h; the calcination temperature is 280-300℃ and the calcination time is 6-8h.
[0014] Secondly, this application provides a micro / nano-scale cobalt tetroxide.
[0015] Preferably, the micro / nano-grade cobalt tetroxide has a cobalt content of 70-73%, a D50 ≤ 0.5 μm, and a specific surface area of 40-110 m². 2 / g.
[0016] The beneficial effects of this application are as follows: Sodium carbonate is used instead of ammonium bicarbonate as a precipitant, avoiding the use of ammonia-containing raw materials, thereby reducing wastewater treatment and environmental protection costs. Simultaneously, cobalt carbonate is used as an intermediate to replace cobalt hydroxide in the preparation of micro / nano-sized cobalt tetroxide. Cobalt carbonate is less prone to oxidation and caking during calcination, resulting in a product with stable cobalt content. Furthermore, by adding a dispersant to the reaction system, the adsorption and steric hindrance of the dispersant inhibit the agglomeration and recrystallization growth of cobalt carbonate particles, avoiding the formation of large particles due to recrystallization characteristics during storage, thus enabling the product to maintain a uniform micro / nano-sized morphology for a long time. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0018] Figure 1 Here is a SEM image of cobalt carbonate obtained in Example 1; Figure 2 Here is a SEM image of the micro / nano-scale cobalt tetroxide obtained in Example 1; Figure 3 Cobalt distribution in the high-nickel ternary cathode prepared in Example 1; Figure 4 The image shows the SEM image of cobalt carbonate obtained in Comparative Example 1. Figure 5 The image shows a SEM image of the micro / nano-scale cobalt tetroxide obtained in Comparative Example 1. Figure 6 The cobalt distribution in the high-nickel ternary cathode prepared for Comparative Example 1; Figure 7 Here is a SEM image of the micro / nano-scale cobalt tetroxide obtained in Example 2; Figure 8 Cobalt distribution in the high-nickel ternary cathode prepared in Example 2; Figure 9 Here is a SEM image of the micro / nano-scale cobalt tetroxide obtained in Comparative Example 2; Figure 10 The cobalt distribution in the high-nickel ternary cathode prepared for Comparative Example 2. Detailed Implementation
[0019] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.
[0020] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0021] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0022] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0023] Unless otherwise explicitly defined and specified herein, all technical and scientific terms used in this application shall have the generally accepted meanings understood by one of ordinary skill in the field of chemical and chemical materials technology (including but not limited to polymer chemistry, inorganic chemistry, organic synthesis, catalysis chemistry, materials processing, and chemical unit operations) based on their professional knowledge and conventional practice. The use of any terminology herein is intended to describe the specific embodiments of this application in the clearest and most accurate manner, so as to fully disclose the technical solution. Such use shall not in any way be construed as a limitation on the scope of the claims, nor does it imply the exclusion of equivalent technical solutions that could be reasonably known by one of skill in the art based on the concept of this application.
[0024] The terms "comprising," "including," "having," "containing," and any grammatical variations or similar expressions used in the specification and claims of this application are all open-ended and non-exhaustive descriptive terms. Their purpose is to explicitly describe the existence of technical features, components, steps, or parts, while explicitly allowing and covering the possibility that other features, components, steps, parts, or any combinations thereof not explicitly listed may exist or be added to the technical solution, as long as such additions do not destroy the integrity and inventiveness of the original technical solution.
[0025] When the terms "embodiments," "some embodiments," or "specific embodiments" are mentioned in the specification, they refer to examples that, in conjunction with the specific parameters, materials, steps, and results described in that section, constitute one or a group of examples for implementing the technical solutions of this application. These embodiments are used for full disclosure and illustrative purposes, not for exhaustive enumeration. Those skilled in the art should understand that, without departing from the overall inventive concept of this application, the various technical features disclosed in different embodiments can be combined, substituted, modified, or deleted to form other implementation methods that are not listed one by one in the specification but also fall within the protection scope of this application.
[0026] Unless otherwise expressly specified and limited, all terms related to chemical process operations, material preparation, processing and analytical testing involved in this application shall be interpreted in the broadest sense based on the conventional understanding of those skilled in the art.
[0027] Regarding performance testing and structural characterization, all testing and characterization methods involved in this application, unless otherwise specified, refer to conventional methods known in the art. Specific testing conditions may be selected and adjusted according to the sample properties and relevant national standards, international standards, or industry-standard methods. Test items may include mechanical properties (such as tensile, bending, and impact strength), thermal properties (such as DSC and TGA analysis), and chemical stability (such as solvent resistance and acid / alkali corrosion resistance). Structural characterization methods may include FT-IR, NMR, XRD, SEM, TEM, and BET. All test results should be understood to be within the allowable range of conventional experimental errors.
[0028] Regarding numerical values and ranges, all parameter ranges expressed in this application in the form of "from a certain value to a certain value" should be understood as explicitly disclosing the endpoints of the range, each specific numerical point between the endpoints, and all sub-ranges formed by any two numerical points within the range. For example, "30℃ to 80℃" discloses 30, 31, ..., 80℃, as well as sub-ranges such as 30-50℃, 45-70℃, etc. When a numerical value is preceded by "about," "approximately," or similar words, it indicates that the numerical value is allowed to have reasonable errors recognized in the art under the measurement or control conditions, which can generally be understood as the deviation allowed by relevant standards or a normal fluctuation range of ±5% or ±10%.
[0029] This application provides a method for preparing micro / nano-scale cobalt tetroxide, comprising the following steps: Using sodium carbonate solution as the base liquid, a dispersant is added and stirred. Then, a cobalt salt solution is added and reacted at a constant temperature. The reaction product (a slurry containing cobalt carbonate) is separated into solid and liquid, dried, calcined, cooled, crushed, and sieved to obtain micro-nano grade cobalt tetroxide.
[0030] In this application, sodium carbonate is used instead of ammonium bicarbonate as a precipitant, avoiding the use of ammonia-containing raw materials and thus reducing wastewater treatment and environmental protection costs. Simultaneously, cobalt carbonate is used as an intermediate to replace cobalt hydroxide in the preparation of micro / nano-sized cobalt tetroxide. Cobalt carbonate is less prone to oxidation and caking during calcination, resulting in a product with stable cobalt content. Furthermore, by adding a dispersant to the reaction system, the adsorption and steric hindrance of the dispersant inhibit the agglomeration and recrystallization of cobalt carbonate particles, avoiding the formation of large particles due to the recrystallization characteristics of cobalt carbonate during storage, allowing the product to maintain a uniform micro / nano-sized morphology for a long time.
[0031] In some embodiments, the concentration of the sodium carbonate solution is 100-200 g / L, and the amount used is 4000-5000 L.
[0032] In this embodiment, within a defined range, the precipitation reaction can be carried out under suitable supersaturation to obtain cobalt carbonate precipitate with uniform particle size. If the sodium carbonate concentration is too low or the amount used is insufficient, the precipitation reaction will be incomplete and the cobalt salt conversion rate will decrease; if the concentration is too high, the supersaturation of the reaction system will increase, resulting in an excessively fast nucleation rate and easy formation of agglomerates.
[0033] In some embodiments, the cobalt salt is cobalt chloride; the concentration of the cobalt salt solution is 90-100 g / L, and the amount used is 1800-2000 L.
[0034] In this embodiment, the concentration and amount of the cobalt salt solution are matched with the concentration and amount of the sodium carbonate solution, jointly determining the supersaturation of the reaction system and the probability of collision between cobalt ions and carbonate ions. If the cobalt salt concentration is too high, the reaction rate is too fast, and the particles grow rapidly after nucleation, making it difficult to control the particle size; if the concentration is too low, the production efficiency decreases.
[0035] In some embodiments, the stirring speed is 400-500 rpm.
[0036] In this application, under a limited stirring rate, the reactants can be mixed rapidly and uniformly, while avoiding excessive shearing that could damage the particle morphology. If the stirring speed is too low, the cobalt salt solution and sodium carbonate solution will mix unevenly, and local concentration differences will lead to inconsistent particle nucleation and growth, easily resulting in a wide particle size distribution. If the stirring speed is too high, it may cause shearing and breakage of the already formed particles or exacerbate collisions and agglomeration between particles.
[0037] In some embodiments, the dispersant is sodium dodecyl sulfonate or sodium hexametaphosphate.
[0038] In this application, sodium dodecyl sulfonate and sodium hexametaphosphate are both anionic dispersants that can be adsorbed onto the surface of cobalt carbonate particles, preventing particle aggregation and recrystallization through electrostatic repulsion and steric hindrance.
[0039] In some embodiments, the amount of dispersant used is 6-10 kg.
[0040] In this application, within this range, the concentration of the dispersant in the reaction system is ensured to be sufficient to coat the surface of the newly formed cobalt carbonate particles, effectively inhibiting recrystallization and the formation of large particles.
[0041] In some embodiments, the isothermal reaction temperature is 40-60°C.
[0042] In this application, within a defined range, the precipitation reaction can be carried out at a moderate rate, which is beneficial to obtaining cobalt carbonate particles with fine particle size and uniform distribution. When the temperature is too low, the reaction rate is slow, there are fewer crystal nuclei, and the particles are prone to growth. When the temperature is too high, it may intensify the thermal motion and collision between particles and increase the tendency to agglomerate.
[0043] In some embodiments, the drying temperature is 100-120℃ and the drying time is 8-10h; the calcination temperature is 280-300℃ and the calcination time is 6-8h.
[0044] In some embodiments, calcination temperature and time directly affect the crystal transformation, specific surface area and particle size of cobalt tetroxide. If the calcination temperature is too low or the time is too short, the cobalt carbonate will not decompose completely, and the product will contain residual cobalt carbonate or insufficient oxidation. If the calcination temperature is too high or the time is too long, the grains will grow excessively, the specific surface area will decrease, and the micro-nano-level high specific surface area characteristics will be lost.
[0045] In some embodiments, this application provides a micro / nano-grade cobalt tetroxide; the cobalt content of the micro / nano-grade cobalt tetroxide is 70-73%, D50 ≤ 0.5 μm, and specific surface area is 40-110 m². 2 / g.
[0046] The following specific embodiments further illustrate this solution.
[0047] Example 1 A method for preparing micro / nano-scale cobalt tetroxide includes the following steps: At room temperature, 5000L of a 200g / L sodium carbonate solution was added to an 8000L reactor as the base liquid. Stirring was started, and heating was initiated, raising the temperature to 40℃. 6kg of sodium dodecyl sulfonate (dispersant) was added to the reactor and stirred until uniformly dissolved. Maintaining a stirring speed of 400rpm, 2000L of a cobalt chloride solution with a cobalt content of 90g / L was introduced into the reactor at a flow rate of 9000L / h. After the introduction was complete, the reaction was maintained at 50℃ for 1 hour, and then stirring was stopped. The product was centrifuged to achieve solid-liquid separation, and then placed in an oven under air atmosphere and dried at 120℃ for 8 hours. After drying, the product was calcined at 280-300℃ for 8 hours, cooled, crushed, and sieved to obtain micro-nano grade cobalt tetroxide samples.
[0048] Example 2 A method for preparing micro / nano-scale cobalt tetroxide includes the following steps: At room temperature, 5000L of a 200g / L sodium carbonate solution was added to an 8000L reactor as a base liquid. Stirring was started, and heating was initiated, raising the temperature to 40℃. 6kg of sodium dodecyl sulfate (dispersant) was added to the reactor and stirred until uniformly dissolved. Maintaining a stirring speed of 400rpm, 2000L of a cobalt chloride solution with a cobalt content of 90g / L was introduced into the reactor at a flow rate of 9000L / h. After the introduction was complete, the reaction was maintained at 40℃ for 1 hour, and then stirring was stopped. The product was centrifuged to achieve solid-liquid separation, and then placed in an oven under air atmosphere and dried at 120℃ for 8 hours. After drying, the product was calcined at 280-300℃ for 8 hours, cooled, crushed, and sieved to obtain micro-nano grade cobalt tetroxide samples.
[0049] Comparative Example 1 A method for preparing cobalt tetroxide includes the following steps: At room temperature, 5000L of a 200g / L sodium carbonate solution was added to an 8000L reactor as the base liquid. Stirring was started, and heating was initiated, raising the temperature to 50℃. While maintaining the stirring speed at 400rpm, 1500L of a 90g / L cobalt chloride solution was introduced into the reactor at a flow rate of 9000L / h. After the introduction was complete, the reaction was maintained at 50℃ for 1 hour, and then stirring was stopped. The product was separated into solid and liquid phases by centrifugation and dried in an oven at 120℃ for 8 hours under air atmosphere. After drying, the product was calcined at 280-300℃ for 8 hours, cooled, crushed, and sieved to obtain the cobalt tetroxide sample.
[0050] Comparative Example 2 A method for preparing cobalt tetroxide includes the following steps: At room temperature, 5000L of a 200g / L sodium carbonate solution was added to an 8000L reactor as the base liquid. Stirring was started, and heating was initiated, raising the temperature to 40℃. While maintaining the stirring speed at 350rpm, 1500L of a 90g / L cobalt chloride solution was introduced into the reactor at a flow rate of 9000L / h. After the introduction was complete, the reaction was maintained at 40℃ for 1 hour, and then stirring was stopped. The product was separated into solid and liquid phases by centrifugation and dried in an oven at 120℃ for 8 hours under air atmosphere. After drying, the product was calcined at 280-300℃ for 8 hours, cooled, crushed, and sieved to obtain the cobalt tetroxide sample.
[0051] Testing and Evaluation The cobalt tetroxide obtained from different embodiments and comparative examples was tested, and the steps are as follows: The obtained micro-nano-grade cobalt tetroxide was mixed uniformly with the prepared 6-series ternary cathode particles at a mass ratio of 2%, and calcined to obtain the cathode material. The obtained cathode material, acetylene black, and PVDF were mixed in a molar ratio of 92:4:4 and added to NMP to obtain a cathode slurry. The cathode slurry was then coated onto aluminum foil to obtain a cathode sheet. Using lithium foil as the anode sheet, CR2430 button batteries were fabricated in an argon-filled glove box. Electrical performance was tested using the Blue Electric testing system under the following conditions: charge and discharge at a rate of 0.5C at room temperature, with a charging cutoff voltage of 4.35V and a discharging cutoff voltage of 2.8V. The first-cycle capacity retention rate was tested under the same conditions as the specific capacity test, calculated from the first-cycle discharge capacity / charge capacity.
[0052] The cobalt content (YS / T 710.1-2009), D50 (GB / T 19077-2016), and specific surface area (BET) of cobalt tetroxide obtained from different embodiments and comparative examples were tested.
[0053] The results are shown in Table 1.
[0054] Table 1 Test Results
[0055] The intermediate and final products were identified, among which... Figure 1 Here is a SEM image of cobalt carbonate obtained in Example 1; Figure 2 Here is a SEM image of the micro / nano-scale cobalt tetroxide obtained in Example 1; Figure 3 Cobalt distribution in the high-nickel ternary cathode prepared in Example 1; Figure 4 The image shows the SEM image of cobalt carbonate obtained in Comparative Example 1. Figure 5 The image shows a SEM image of the micro / nano-scale cobalt tetroxide obtained in Comparative Example 1. Figure 6 The cobalt distribution in the high-nickel ternary cathode prepared in Comparative Example 1; Figure 7 Here is a SEM image of the micro / nano-scale cobalt tetroxide obtained in Example 2; Figure 8 Cobalt distribution in the high-nickel ternary cathode prepared in Example 2; Figure 9 Here is a SEM image of the micro / nano-scale cobalt tetroxide obtained in Comparative Example 2; Figure 10 The cobalt distribution in the high-nickel ternary cathode prepared for Comparative Example 2.
[0056] The above results demonstrate that using sodium carbonate instead of ammonium bicarbonate as a precipitant in this application avoids the use of ammonia-containing raw materials, thereby reducing wastewater treatment and environmental protection costs. Simultaneously, using cobalt carbonate as an intermediate to replace cobalt hydroxide in the preparation of micro / nano-sized cobalt tetroxide ensures that cobalt carbonate is less prone to oxidation and agglomeration during calcination, resulting in a product with stable cobalt content. Furthermore, by adding a dispersant to the reaction system, the adsorption and steric hindrance of the dispersant inhibit the agglomeration and recrystallization of cobalt carbonate particles, avoiding the formation of large particles due to recrystallization characteristics during storage. This allows the product to maintain a uniform micro / nano-sized morphology for a long time, thus enabling industrial-scale production.
[0057] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing micro / nano-scale cobalt tetroxide, characterized in that, Includes the following steps: Using sodium carbonate solution as the base liquid, a dispersant is added and stirred. Then, a cobalt salt solution is added and reacted at a constant temperature. The reaction product is separated into solid and liquid, dried, calcined, cooled, crushed, and sieved to obtain micro-nano grade cobalt tetroxide.
2. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The concentration of the sodium carbonate solution is 100-200 g / L, and the dosage is 4000-5000 L.
3. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The cobalt salt is cobalt chloride; the concentration of the cobalt salt solution is 90-100 g / L, and the dosage is 1800-2000 L.
4. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The stirring speed is 400-500 rpm.
5. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The dispersant is sodium dodecyl sulfonate or sodium hexametaphosphate.
6. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The amount of the dispersant used is 6-10 kg.
7. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The temperature of the isothermal reaction is 40-60℃.
8. The method for preparing micro / nano-scale cobalt tetroxide according to claim 1, characterized in that, The drying temperature is 100-120℃ and the drying time is 8-10h; the calcination temperature is 280-300℃ and the calcination time is 6-8h.
9. A micro / nano-scale cobalt tetroxide obtained by the preparation method according to any one of claims 1-8.
10. The micro / nano-scale cobalt tetroxide according to claim 9, characterized in that, The micro / nano-grade cobalt tetroxide has a cobalt content of 70-73%, a D50 ≤ 0.5 μm, and a specific surface area of 40-110 m². 2 / g.